Single or combined use of intermittent fasting and probiotics reduce Campylobacter colonization in the murine gut - Acik, M. N.; Dogu, U. G.; Geyik, A.; Girgin, M.; Ulucan, A.; Karagulle, B.; Cetinkaya, B. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2025)
The objective of the present study was to investigate the impact of single or combined use of intermittent fasting and probiotics, which have been recommended as an alternative to anti-biotics in recent years due to their proven efficacy, against Campylobacter colonization in mice. For this purpose, mice infected with Campylobacter jejuni were divided into groups and exposed to intermittent fasting and probiotics, alone and together. At the end of the experimental study, ileum and cecum contents were obtained for microbiological analyzes, and stomach and intestinal tissue samples were collected for histopathological analyzes. It was determined that the level of C. jejuni colonization in the ileum and cecum of mice in the positive control group (PC group) was significantly higher than in the other groups (p<0.05). It was also determined that the level of C. jejuni colonization in the ileum of mice in the probiotic and intermittent fasting group (PB +IF group) was lower than in the other groups and the difference was statistically significant (p<0.05). As a result of the histological analyzes, mild inflammatory reaction was observed to occur in the stomach and intestinal tissues of the animals in the experimental groups, and the severity of the inflammation was lower in the PB +IF group than in the other groups. The findings of this study indicate that single or combined use of intermittent fasting and probiotics may represent a safe and feasible strategy for the control of Campylobacter infections.
Keywords: Campylobacter jejuni; intermittent fasting; mice; probiotic